Pengaruh fortifikasi ekstrak kulit buah naga super merah (Hylocereus costaricensis) terhadap kandungan antioksidan tape singkong kuning (Manihot utilissima Pohl) - Ni’matusyukriyah Ni’matusyukriyah; Muh. Aniar Hari Swasono (Program Studi Ilmu dan Teknologi Pangan, Universitas Yudharta, Pasuruan, 2020)
The super red dragon fruit peels waste that is under utilized by the people and prefers to be thrown away, has a lot of nutrient content over the fruit flesh, and the decline in people's interest in fermented cassava causes the loss of cassava farmers. Therefore, it is necessary to do research on the innovation of fermented cassava which also adds value to the nutritional content. This study aims to determine the effect of the addition of super red dragon fruit peels percentage and the addition of yeast percentage to antioxidant activity. The method used in the study of the manufacture of antioxidant fortified yellow cassava using factorial Randomized Block Design (RBD) consisting of 2 factors, the first factor consists of 3 levels and the second factor consists of 3. Of the two factors obtained 6 combinations of treatments. Each treatment was repeated three times, so that 18 treatment combinations were obtained. Tests carried out include physicochemical tests (antioxidant activity, pH, color intensity) and organoleptic tests (color, aroma, taste and texture). Analysis of physicochemical test using ANOVA. If it is significantly different, then it is followed by the Tukey method and to find the best treatment according to physicochemical parameters using the Zelleny method. Organoleptic test analysis uses the Friedman test and to find the best treatment according to organoleptic parameters using Effectiveness Index. The results of this study indicate that the combination treatment of the addition of super red dragon fruit peels by 30% w/v and the percentage yeast of 0.4% w/w is the best results according to physicochemical test parameters with the following characteristics: DPPH% Inhibition (83.115%), pH (4.53), L color intensity (50.2), Color intensity a + (47.7), Color intensity b + (12,32). The best treatment organoleptic test was obtained from a combination of treatment the percentage of the addition of super red dragon fruit peels by 30% b / v and the percentage of yeast 0.4% b / b provided that the average color organoleptic test score was 3.97 (likes), flavor 3 , 77 (likes), texture 2.77 (enough), taste 3.5 (likes).